Quo Vadis Diplomasi Parlemen Indonesia: Kepemimpinan DPR RI Pada Forum Asean Inter-Parliamentary Assembly (AIPA) Tahun 2011-2012 - Bagus Firdaus, Muhammad Jullyo (Global and Policy Journal of International Relations, 2021)
ABSTRAK Aktor parlemen dalam negara seringkali kurang dilihat sebagai aktor penting dalam Hubungan Internasional. Di era kontemporer, studi diplomasi dalam Hubungan Internasional mengalami perkembangan cukup pesat. Paper ini membahas mengenai penerapan diplomasi parlemen Indonesia (DPR RI) ketika menjadi pemimpin Asean Inter-Parliamnetary Assembly tahun 2011 hingga 2012. Diikuti dengan kepemipinan Indonesia (eksekutif) di ASEAN pada rentang tahun yang sama. Adanya pelaksanaan diplomasi parlemen Indonesia merupakan manifestasi dari doktrin Menteri Luar Negeri Hassan Wirajuda, yang massif dikampenyakan pada periode 2001 hingga 2009 akan pentingnya diplomasi total bagi politik luar negeri Indonesia dalam mencapai kepentingan nasional.  Pembahasan pada paper ini berfokus pada bagaimana posisi diplomasi parlemen Indonesia vis-à-vis dengan eksekutif dalam regional Asia Tenggara pada forum AIPA periode 2011-2012.  Penelitian ini berupaya menjabarkan akan posisi DPR RI sebagai representasi Indonesia di tingkat parlemen regional Asia Tenggara, sekaligus menafsirkan bahwa diplomasi total sebagai diplomasi multi-jalur sangat berpengaruh bagi diplomasi Indonesia dalam lingkungan internasional. Dalam penerapan diplomasi multi-jalur, penulis mengartikulasikan DPR RI sebagai diplomasi jalur 11/2. Penelitian ini, memberikan pandangan penting akan urgensi diplomasi total bagi politik luar negeri Indonesia melalui pelaksanaan diplomasi parlemen, ditemukan bahwa dalam mencapai kepentimgan nasional aktor legislatif dan eksekutif mendukung upaya pencapaian kepentingan nasional.   Kata-Kata Kunci: diplomasi parlemen, DPR RI, Asean Inter-Parliamentary Assembly, diplomasi total, diplomasi multi-jalur.   The Position of Parliament in state often not seen as important actors in international relations. In the contemporary era, diplomatic studies in International Relations have developed quite rapidly. This paper discusses the implementation of Indonesian parliamentary diplomacy (DPR RI) when it became the leader of the ASEAN Inter-Parliamentary Assembly from 2011 to 2012. It Followed by the Indonesian leadership (executive) in ASEAN in the same year. The implementation of Indonesian parliamentary diplomacy is a manifestation of Foreign Minister Hassan Wirajuda's doctrine, which was massively expressed in the period 2001 to 2009 on the importance of total diplomacy for Indonesia's foreign policy in achieving national interests. The discussion in this paper focuses on the diplomatic position of the Indonesian parliament vis-à-vis with executives in the Southeast Asia region at the AIPA forum for the period 2011-2012. This research seeks to elaborate on the position of the Indonesian Parliament as a representation of Indonesia at the regional parliamentary level in Southeast Asia, as well as interpreting that total diplomacy as multi-track diplomacy is very influential for Indonesian diplomacy in the international environment. In the application of multi-track diplomacy, the writer articulates the DPR RI as track 11/2 diplomacy. This research, providing an important view of the urgency of total diplomacy for Indonesia’s foreign policy through the implementation of parliamentary diplomacy. And also found that in achieving national interests the legislative and executive actors supported efforts to achieve national interests. Keywords: parliamentary diplomacy, The House Of Representatives Of The Republic Of Indonesia, Asean Inter-Parliamentary Assembly, total diplomacy, multi-track diplomacy.